2003
DOI: 10.1007/s00216-003-2028-5
|View full text |Cite
|
Sign up to set email alerts
|

An uncertainty budget for trace analysis by isotope-dilution ICP-MS with proper consideration of correlation

Abstract: Isotope-dilution mass spectrometry (IDMS) is considered to be a method without significant correction factors. It is also believed that this method is well understood. But unfortunately a large number of different uncertainty budgets have been published that consider different correction factors. These differences lead to conflicting combined uncertainties especially in trace analysis. It is described how the known correction factors must be considered in the uncertainty budget of values determined by IDMS com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 51 publications
0
31
0
Order By: Relevance
“…Moser et al (2003) applied this, together with analysis of variance (ANOVA) and demonstrated that the uncertainty budgets of the PGE concentrations in UB-N were dominated by sample inhomogeneity. It is more complicated to apply the Ingamells approach to analyte concentrations at trace levels.…”
Section: Methods Validation For Low Abundance Samplesmentioning
confidence: 99%
“…Moser et al (2003) applied this, together with analysis of variance (ANOVA) and demonstrated that the uncertainty budgets of the PGE concentrations in UB-N were dominated by sample inhomogeneity. It is more complicated to apply the Ingamells approach to analyte concentrations at trace levels.…”
Section: Methods Validation For Low Abundance Samplesmentioning
confidence: 99%
“…Several authors have discussed the effects of correlation among the variables in IDMS uncertainty propagation [9,16]. In these accounts, the correlation of isotope ratios was noted.…”
Section: Theorymentioning
confidence: 98%
“…In 2003, Hibbert discussed the effects of signal correlation in analytical chemistry ratio measurements which share components in the numerator and denominator raising the question of whether or not correlation effects appear in isotope-dilution mass spectrometry [17]. The same year Moser et al outlined uncertainty propagation in isotope dilution where a correlation between the isotope ratios was considered [9]. However, these are exceptions to the common error analysis that treats all isotopic intensities as independent variables for error propagation purposes [18][19][20][21][22][23][24].…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…In 2001 Nelms et al critically reviewed the most commonly used methods in ICPMS [80]. Moser et al analysed the influence of dead time on the IDMS result and its uncertainty [81]. They found the coherence unexpectedly difficult to understand as several minima for the uncertainty contribution occurred depending on the chosen scenario.…”
Section: Sources Of Bias or Errormentioning
confidence: 99%